DETERMINAN HARGA SAHAM: PERAN SENTIMEN INVESTOR, TINGKAT INFLASI, DAN PENGUNGKAPAN SUSTAINABILITY REPORT - Ratih Wahyuningsih; Desy Nur Pratiwi; Suhesti Ningsih (CV. Denasya Smart Publisher, 2026)
This study examines the influence of investor sentiment, inflation rates, and sustainability report disclosures on stock prices of energy sector companies listed on the Indonesia Stock Exchange from 2022 to 2024. This study employs a quantitative approach, with data collected using the documentation method. The sampling technique in this study used purposive sampling, resulting in a sample of 24 companies with 58 data points. The data used were secondary data, specifically financial statements, annual reports, stock prices, and inflation data. The data sources in this research come from the official website of the Indonesian Stock Exchange, namely www.idx.co.id and the official website of BPS Statistics Indonesia, namely www.bps.go.id. The data analysis methods used included descriptive statistical tests, tests of classical assumptions, and hypothesis testing, which consisted of multiple linear regression analysis, the F-test, the t-test, and the multiple coefficients of determination test. The test results indicate that the sustainability report disclosure variable influences stock prices. However, when analyzed individually, the investor sentiment and inflation rate variables do not influence stock prices. These findings highlight the importance of sustainability report disclosure as a factor of investors consider in making investment decisions, given that such disclosure has been shown to influence stock prices.